Participant and Public Involvement in Refining a Peer-Volunteering Active Aging Intervention: Project ACE (Active, Connected, Engaged). (6th December 2016) - Withall, Janet; Thompson, Janice L; Fox, Kenneth R; Davis, Mark; Gray, Selena; de Koning, Jolanthe; Lloyd, Liz; Parkhurst, Graham; Stathi, Afroditi
Abstract: Background: Evidence for the health benefits of a physically active lifestyle among older adults is strong, yet only a small proportion of older people meet physical activity recommendations. A synthesis of evidence identified "best bet" approaches, and this study sought guidance from end-user representatives and stakeholders to refine one of these, a peer-volunteering active aging intervention. Methods: Focus groups with 28 older adults and four professional volunteer managers were conducted. Semi-structured interviews were conducted with 9 older volunteers. Framework analysis was used to gauge participants' views on the ACE intervention. Results: Motives for engaging in community groups and activities were almost entirely social. Barriers to participation were lack of someone to attend with, lack of confidence, fear of exclusion or "cliquiness" in established groups, bad weather, transport issues, inaccessibility of activities, ambivalence, and older adults being "set in their ways". Motives for volunteering included "something to do, " avoiding loneliness, the need to feel needed, enjoyment, and altruism. Challenges included negative events between volunteer and recipient of volunteering support, childcare commitments, and high volunteering workload. Conclusion: Peer-volunteering approaches have great potential for promotion of active aging. The systematic multistakeholder approach adopted in this study led to important refinements of the original ACE intervention. The findings provide guidance for active aging community initiatives highlighting the importance of effective recruitment strategies and of tackling major barriers including lack of motivation, confidence, and readiness to change; transport issues; security concerns and cost; activity availability; and lack of social support.